2016
DOI: 10.1088/0741-3335/58/10/103001
|View full text |Cite
|
Sign up to set email alerts
|

Applications of laser wakefield accelerator-based light sources

Abstract: Laser-wakefield accelerators (LWFAs) were proposed more than three decades ago, and while they promise to deliver compact, high energy particle accelerators, they will also provide the scientific community with novel light sources. In a LWFA, where an intense laser pulse focused onto a plasma forms an electromagnetic wave in its wake, electrons can be trapped and are now routinely accelerated to GeV energies. From terahertz radiation to gamma-rays, this article reviews light sources from relativistic electrons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
132
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(139 citation statements)
references
References 309 publications
2
132
0
Order By: Relevance
“…Our simulations demonstrate stable low-dissipation pulse propagation through many The formed laser cavity propagates ten Rayleigh lengths (∼ 250λ) for a 0 = 24, R L = 2λ, 8 and n e = 0.1n c from entering the plasma to the distance where the pulse depletes. We found that the estimate of the characteristic depletion scale L d ≈ Ln e /n c 90λ from the effect of pulse depletion [21] agrees with our simulation result similar to that in Ref.…”
Section: Self-trapping Regimementioning
confidence: 77%
“…Our simulations demonstrate stable low-dissipation pulse propagation through many The formed laser cavity propagates ten Rayleigh lengths (∼ 250λ) for a 0 = 24, R L = 2λ, 8 and n e = 0.1n c from entering the plasma to the distance where the pulse depletes. We found that the estimate of the characteristic depletion scale L d ≈ Ln e /n c 90λ from the effect of pulse depletion [21] agrees with our simulation result similar to that in Ref.…”
Section: Self-trapping Regimementioning
confidence: 77%
“…The acceleration of electrons by schemes like laser-wakefield acceleration [4,5], mainly from gaseous targets, allows a high repetition-rate and debris-free environment. In contrast, the acceleration of protons and ions by schemes like target-normal-sheath acceleration [6,7] or radiation-pressure acceleration [8,9] is based on solid density targets, which come with several drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…The pursuit of compact γ-ray sources is motivated by many applications in fundamental science, industry, and medicine [1,2]. High-energy γ-ray radiation has become an immensely useful tool for probing hot dense matter [3], photonuclear spectroscopy [4], inspection of nuclear waste [5], material synthesis [6], and cancer therapy [7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to conventional γ-ray sources based on large-scale and costly particle accelerators [8,9], the γ-ray source based on an all-optical approach is much more compact because in laser-plasma interaction process, extremely large accelerating fields-above 100 GV m −1 -can be produced and lead to high-energy electron beams in an ultrashort distance. In addition, laser-based γ-ray source possesses unique properties, such as ultrashort duration, ultrahigh brilliance, and small source size [1,2], which potentially makes it possible to realize a tabletop γ-ray source with much higher spatiotemporal resolution than the conventional ones.…”
Section: Introductionmentioning
confidence: 99%